Single-Cell Sequencing of Immune Cell Heterogeneity in IgG4-Related Disease - Wu, Xunyao; Peng, Yu; Li, Jieqiong; Zhang, Panpan; Liu, Zheng; Lu, Hui; Peng, Linyi; Zhou, Jiaxin; Fei, Yunyun; Zeng, Xiaofeng; Zhao, Yan; Zhang, Wen (Frontiers in Immunology, 2022)
Background The IgG4-related disease (IgG4-RD) is considered as an immune-mediated disorder with fibrotic manifestations. So far, little is known about the transcriptional profiles of immune cell subsets at single-cell level. we performed single-cell sequencing to to exploit specific cell subpopulations and pathways in peripheral blood mononuclear cells (PBMCs) of IgG4-RD. Methods Single-cell sequencing was performed in the PBMCs from 4 IgG4-RD patients and 3 HCs. Functional enrichment, cell and cell analysis were performed through re-clustering of PBMCs and was used to understand functional pathways and intercellular communication networks in IgG4-RD. Western blot and flowcytometry were then conducted to verify sequencing and functional enrichment results. Results We identified 4 major cell types, along with 21 subtypes. Further subclustered B cells demonstrated higher plasma B cell proportions with increased glycolysis//gluconeogenesis activity in IgG4-RD. Re-clustering myeloid cells showed significantly higher EGR1 and CD36 expression on CD14+ monocytes of IgG4-RD and validated by western blot analysis. Moreover, positive regulation of TNF production pathways was found enriched in CD14+ monocytes of IgG4-RD. We performed in vitro stimulation and found that CD14+ monocytes of IgG4-RD secreted higher levels of TNF-up stimulation. Notably, the proportions of CD8 Central Memory T (TCM) and TIGIT+ CD8 Cytotoxic T (CTL) increased in IgG4-RD patients compared with HCs. Further interaction analysis showed that BAFF signaling pathways from myeloid cells subsets to B cells were enriched. Conclusion our data provide further understanding of the cellular heterogeneity and transcriptional features involved in the pathogenesis of IgG4-RD and offer important clinical implications.